A psychosocial bouldering intervention improves the well-being of young refugees and adolescents from the host community in Lebanon: results from a pragmatic controlled trial - Luttenberger, Katharina; Baggenstos, Beat; Najem, Charbel; Sifri, Charles; Lewczuk, Piotr; Radegast, Anne; Rosenbaum, Simon (Conflict and Health, 2024)
Background: Mental health and psychosocial support (MHPSS) is increasingly considered vital for addressing the needs of displaced communities. The mental health of young people in Lebanon, including members of the host community and refugees, has been severely affected by multiple crises. Physical activity (PA) is an effective means for enhancing mental health, but evidence of PA’s impact on mental health among forcibly displaced populations is still emerging and often varies widely across studies. Method: In this waitlist-controlled study, we examined the effectiveness of an 8-week psychosocial bouldering group intervention offered by the nonprofit organization ClimbAID on psychological well-being, distress, self-efficacy, and social cohesion in a group of mostly Syrian refugee adolescents residing in the Bekaa Valley, Lebanon. The intervention consisted of 8 sessions and took place once a week for 2 h in a group of up to 12 adolescents with 2 trained facilitators and up to 2 volunteers, supervised by a climbing instructor and a social worker. Multilevel analyses were performed for all outcomes. Results: 233 people were included in the study. The dropout rate was approximately 33%. The IG improved significantly more than the waitlist group in terms of overall mental well-being and psychological distress. Group allocation was a significant predictor of improvements in mental well-being and psychological distress and showed a trend toward predicting self-efficacy. There was no positive impact of the intervention on social cohesion. Conclusions: Even in complex humanitarian settings of forced displacement, a psychosocial bouldering intervention reduces psychological distress and increases well-being in a mixed group of host and refugee youth in Bekaa, Lebanon. Trial registration: Prospectively registered with ISRCTN 13005983, registered April 1st, 2022.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Bouldering; Climbing therapy; Forced displacement; Host community; Lebanon; MHPSS; Physical activity; Refugee; Syria